If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (w + 2)(w + 1) = 12 Reorder the terms: (2 + w)(w + 1) = 12 Reorder the terms: (2 + w)(1 + w) = 12 Multiply (2 + w) * (1 + w) (2(1 + w) + w(1 + w)) = 12 ((1 * 2 + w * 2) + w(1 + w)) = 12 ((2 + 2w) + w(1 + w)) = 12 (2 + 2w + (1 * w + w * w)) = 12 (2 + 2w + (1w + w2)) = 12 Combine like terms: 2w + 1w = 3w (2 + 3w + w2) = 12 Solving 2 + 3w + w2 = 12 Solving for variable 'w'. Reorder the terms: 2 + -12 + 3w + w2 = 12 + -12 Combine like terms: 2 + -12 = -10 -10 + 3w + w2 = 12 + -12 Combine like terms: 12 + -12 = 0 -10 + 3w + w2 = 0 Factor a trinomial. (-5 + -1w)(2 + -1w) = 0Subproblem 1
Set the factor '(-5 + -1w)' equal to zero and attempt to solve: Simplifying -5 + -1w = 0 Solving -5 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1w = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1w = 0 + 5 -1w = 0 + 5 Combine like terms: 0 + 5 = 5 -1w = 5 Divide each side by '-1'. w = -5 Simplifying w = -5Subproblem 2
Set the factor '(2 + -1w)' equal to zero and attempt to solve: Simplifying 2 + -1w = 0 Solving 2 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1w = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1w = 0 + -2 -1w = 0 + -2 Combine like terms: 0 + -2 = -2 -1w = -2 Divide each side by '-1'. w = 2 Simplifying w = 2Solution
w = {-5, 2}
| 5x-2=12+3x | | 5x-2=12+3 | | x-1=2x-8 | | h+100=1000 | | -3x+3=-6+6 | | 4x-15=6x-27 | | 16=4-3(h-13) | | 3(x+4)-2(x+4)=4 | | x-10=-5x+32 | | m-9=-27 | | 6-2x=5x+9 | | 15hy+14=2(5y+6) | | -3c(+4)-2=7 | | L=8-6R+5k | | 3x+14=84 | | 10(x+3)=-5 | | 3(8y-2)=5(2y+4) | | n+11/3=52/9 | | 2x+12=45 | | 14=x-9 | | 18n=8+17n | | -25+1=x | | -5(v+1)=7v-3+2(2v+1) | | q-2=-16 | | 5x+2=9x | | 2.4x+47.3=15.2-8.3x | | n+32/3=57/9 | | 4-2x=8+x/2 | | 4x(x-5)=-12 | | 4x+y=132 | | 18-.66x=6 | | 6+4s-3=9s+11-7s |